Vehicular energy electrification in Palestine oriented to enhance socio-economic development: A focus on solar electrical energy potential for powering PHEVs and EVs - Sughayyer, M.; Arafeh, D. (Palestine Polytechnic University, 2025)
This contribution is a policy recommendation paper that focuses on the enormously positive implications of vehicular energy transition on local socio-economic development, if some tailored and incentivizing policies aimed to encourage public private partnerships and projects directed to develop this highly energy-dependent sector are adopted. PENRA website reports that in 2020 about 87% of energy comes from Israeli sources, and energy consumption by vehicular sector is 42% of the total energy [1]. Given its largest size of energy consumption and will increase in size as the registered vehicles increases, which will worsen the current situation of dependency on supplies from Israel, the Palestinian Authorities (PA) needs to design and implement policies aimed to encourage renewable energy production and usage in all forms, especially solar electrical power for vehicular sector usage, knowing that only 4% of the total electric power is renewable according to Palestinian Energy and Natural Resources Authority (PENRA) statistics in 2021 [1]. Fortunately, vehicle modern technologies facilitate the adoption of transport sector electrification policies such as Plug-in Hybrid Electric Vehicles (PHEVs) and Battery Drive Electric Vehicles (EVs). Finally, PA through tailored and incentivizing policies aimed to encourage public-private partnerships directed to develop PV plants, through reduction of wheeling costs and taxation, will increase the employment of young graduates and helps to develop remote areas. While this allowed to happen and with the increase of the economic cycle size, the PA revenues will certainly increase from all the benefited sectors exceeding all the exempted costs.
Number of pages: 5, 2025 Engineering for Palestine Conference (ENG4PAL) PPU, Hebron, Palestine, September 29-30, 2025
Keywords: Vehicular, energy, electrification, Palestine, oriented, enhance, socio-economic, development, focus, solar, electrical, energy, potential, powering, PHEVs, EVs